Sustainability Indices and ESG-ratings, the Impact on Corporate Sustainability : a case study using the perspective of a fast-growing Swedish bank - Magnér, Sofia (SLU/Dept. of Economics, 2020)
The sustainability indices and ratings have expanded over the past decade. Due to the growing perception of social responsibility and environmental issues, measurement of the non-financial performance of corporations has become essential and pressure from stakeholders has resulted in new business strategies. Several rating agencies have provided measurements instrument and the market seem to be a smorgasbord of alternatives. The question is, how do companies perceive this development, and do they share similar values? Processes used to assess corporations’ sustainability performance are not consistent (Delmas & Blass, 2010). Since there are no standardised processes, it entails numerous interpretations considering Corporate Sustainability, which has caused heterogeneity of Corporate Sustainability Assessment. This has in turn resulted in a vast and chaotic universe of services that qualify companies in terms of sustainability and ESG-factors (Diez-Canamero et al., 2020). This study provides an insight into what impact sustainability indices may have on Corporate Sustainability standards, and how companies adapt to the requirements. To accomplish a deeper understanding of this dilemma, a comparison between the indices and a chosen company is discussed. The study aims to contribute to the literature in the field of Corporate Sustainability, using the perspective of both sustainability indices and a fast-growing company. In order to fulfil the aim, the research was conducted by a qualitative method, in which empirical data was gathered by ethnography, in combination with a semi-structured interview. The data collection was carried out based on a theoretical framework including Standards, Corporate Sustainability, Created Shared Value (CSV), Corporate Sustainability Assessment (CSA), and the Stakeholder theory. The conclusions of this study suggest that the number of sustainability indices may cause an obstacle for sustainable development rather than improved sustainability. At present, the number of sustainability indices and ESG-ratings provides an overflow of measurements which tends to create a diminished commitment in the evaluated organisation.